Non‐specific accumulation of glycosphingolipids in GNE myopathy. Issue 2 (18th October 2013) - Patzel, Katherine A.; Yardeni, Tal; Le Poëc‐Celic, Erell; Leoyklang, Petcharat; Dorward, Heidi; Alonzi, Dominic S.; Kukushkin, Nikolay V.; Xu, Bixue; Zhang, Yongmin; Sollogoub, Matthieu; Blériot, Yves; Gahl, William A.; et al.
Abstract: Background: UDP‐GlcNAc 2‐epimerase/ManNAc 6‐kinase (GNE) is a bifunctional enzyme responsible for the first committed steps in the synthesis of sialic acid, a common terminal monosaccharide in both protein and lipid glycosylation. GNE mutations are responsible for a rare autosomal recessive neuromuscular disorder, GNE myopathy (also called hereditary inclusion body myopathy). The connection between the impairment of sialic acid synthesis and muscle pathology in GNE myopathy remains poorly understood. Methods: Glycosphingolipid (GSL) analysis was performed by HPLC in multiple models of GNE myopathy, including patients' fibroblasts and plasma, control fibroblasts with inhibited GNE epimerase activity through a novel imino sugar, and tissues of Gne M712T/M712T knock‐in mice. Results: Not only neutral GSLs, but also sialylated GSLs, were significantly increased compared to controls in all tested models of GNE myopathy. Treatment of GNE myopathy fibroblasts with N‐acetylmannosamine (ManNAc), a sialic acid precursor downstream of GNE epimerase activity, ameliorated the increased total GSL concentrations. Conclusion: GNE myopathy models have increased total GSL concentrations. ManNAc supplementation results in decrease of GSL levels, linking abnormal increase of total GSLs in GNE myopathy to defects in the sialic acid biosynthetic pathway. These data advocate for further exploring GSL concentrations as an informative biomarker, not only for GNE myopathy, but also for other disorders of sialic acid metabolism.